2010
DOI: 10.1016/j.jtcvs.2009.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different annuloplasty rings on anterior mitral leaflet dimensions

Abstract: OBJECTIVE To assess the effects of annuloplasty rings (ARs) on anterior mitral leaflet (AML) dimensions. METHODS Sixteen radiopaque markers were sutured evenly spaced over the surface of the AML in 57 sheep. Size 28 mm Cosgrove (n=11), rigid saddle-shaped AR (RSAR) (n=12), Physio (n=12), IMR-ETlogix (n=10) and GeoForm (n=12) rings were implanted in a releasable fashion. Under acute open-chest conditions, 4-D marker coordinates were measured using biplane videofluoroscopy with the AR inserted and after AR rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 20 publications
(20 reference statements)
1
34
1
Order By: Relevance
“…These results appear to be reasonable, taking the ring rigidity into account. Moreover, it has been reported that even a flexible band could not preserve any contraction in the AP and CC directions of the annulus postoperatively [8]. In our study, both saddle-shaped rings were also unable to preserve any annular dynamics.…”
Section: Commentcontrasting
confidence: 66%
See 1 more Smart Citation
“…These results appear to be reasonable, taking the ring rigidity into account. Moreover, it has been reported that even a flexible band could not preserve any contraction in the AP and CC directions of the annulus postoperatively [8]. In our study, both saddle-shaped rings were also unable to preserve any annular dynamics.…”
Section: Commentcontrasting
confidence: 66%
“…According to those reports, maintaining or recovering the physiologic three-dimensional annular shape can reduce the leaflet strain and is important for the long-term valve function. However, it was reported that neither the anteroposterior nor the commissure-to-commissure dimensions change throughout the cardiac cycle after ring implantation with a saddle, flat, or even flexible ring in an acute animal model [8]. On the other hand, it was reported that only the annular folding dynamics were preserved by a flexible band [4].…”
mentioning
confidence: 99%
“…Displacements were imposed to the nodes on the annulus, whose original commissurecommissure diameter was of 45 mm, to adapt its shape to the profile of a 40 mm total rigid ring, representative of the most commonly implanted type of annular prostheses. 3 This ring had a D-shaped design, with the straight portion of the D corresponding to the anterior portion of the ring, an approximately 4:3 ratio between commissural and septo-lateral ring diameters, and a slightly non-planar profile. Nodal displacements were set assuming that the change in annular length was uniform in the intertrigonal tract of the annulus and in the posterior one.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…1(d)). The D-shaped annulus and its dimensions were based on the nominal profile of a native MV [22,23,29,32]. For the Dshaped annulus, the flat portion was positioned such that it was proximal to the aorta, matching anatomical in vivo orientation.…”
Section: Mitral Annulus Geometriesmentioning
confidence: 99%
“…This nontraditional mitral PHV design is based on the assumption that mimicking the unaltered native MV annulus would be optimal for restoring normal cardiac function. In addition, majority of mitral annuloplasty rings employ D-shaped annulus geometry [27][28][29]. Most annuloplasty rings used in present day clinical procedures are designed considering structural factors, such as leaflet stress distribution during annulus interaction with the time-varying motion of the left heart complex, and eventual surgical selection is made based on matching with patient-specific anatomy and ease of positioning.…”
Section: Introductionmentioning
confidence: 99%